FACTORS CONTRIBUTING TO NON-ADHERENCE TO MEDICATIONAMONG TYPE 2 DIABETES MELLITUS IN PATIENTS ATTENDING TERTIARY CARE HOSPITAL IN SOUTH INDIA - S, Divya; Nadig, Pratibha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The aim was to determine the non-adherence to medication and to assess the factors affecting the same among the Type 2 diabetes mellitus (DM) patients in a tertiary care hospital in South India. Methods: A cross-sectional study was carried out on 150 known Type 2 DM patients. Eight item Morisky Medication adherence questionnaire was used to assess adherence. A validated questionnaire was used to collect information on factors influencing non-adherence namely age, gender, literacy, duration of diabetes, complications, economic problems, patient awareness about their medication and side-effects, adverse drug reactions and advice on exercise and diet. The percentage of non-adherence and factors contributing to non-adherence were analyzed with descriptive statistics and Chisquare test using IBM SPSS version 21. Results: More than two-thirds of the patients (69.3%) were males. The overall prevalence of therapeutic non-adherence was seen in 82 patients (54.66%). Among the non-adherant patients, 16 patients (17.08%) were illiterates. 32 patients (39.02%) had economic problems to buy prescribed medications, 53 (64.63%) of them had lack of information about prescribed medications was seen, 37 (45.12%) patients were not aware of the side effects of the prescribed medication, 59 (71.95%) patients were not aware of what happens on missing medications regularly, 39 (47.56%) of them were not able to visit physician regularly for consultation, 52 (63.45%) and 49 (59.75%) of patients were not performing exercise and not following advise on diet respectively. Conclusion: Non-adherance to medications in Type 2 DM patients is due to inadequate patient knowledge and awareness about the importance of adherence in the diabetes management. Therefore, there is a definite need to improve patient adherence by improving the health care system and health education to patients and their families. Keywords: Type 2 diabetes mellitus, Factors, Non-adherence. Â 